Aldehyde-Assisted Alkoxysilane Condensation to Form Siloxane Bond: A New Process for Curing Alkoxy-Functional Silicone Resins - Sławomir Rubinsztajn; Urszula Mizerska; Jan Kurjata; Małgorzata Kwiatkowska; Marek Cypryk (Molecules)
The formation of the siloxane bond is one of the most important reactions used in silicone chemistry and technology. In this paper, a new process for the condensation of alkoxy-functional silanes to form a siloxane bond is presented. The new reaction is catalyzed by a Ge(II)+ complex stabilized by pentamethylcyclopentadiene with a weakly coordinated anion, tetrakis(pentafluorophenyl)borane. A mechanistic study of this new condensation process using model alkoxy-functional silanes and propionaldehyde is completed. It is established that the quantitative conversion of alkoxysilanes to the siloxane bond requires stoichiometric amounts of aldehyde. It is also found that paraldehyde can serve as a convenient, higher boiling source of acetaldehyde for the condensation of alkoxysilanes. The results obtained, supported by DFT calculations, allow for us to formulate the mechanism of this reaction.